Disappearing ‘formal organization’: How organization studies dissolved its ‘core object’, and what follows from this - du Gay, Paul (Current sociology, 2020)
This article addresses itself to accounting for how and why the situation has arisen whereby much, though by no means all, of what self-identifies as organizational analysis – whether in sociology or organization studies – isn’t actually organizational, and to exploring what follows from this. The article argues that the specificity of ‘organizational analysis’ – which requires its proponents to think (and, indeed, act) ‘organizationally’ – has been returned to the amorphous world of ‘social explanation’. The article therefore attempts to highlight the manner in which the tropes of social explanation deployed within contemporary sociology and organization studies reduce ‘formal organization’ to the status of a social container. In making this case, the article commends an alternative stance towards organization that precisely eschews ‘talking about organizations’ epiphenomenally. It does so by seeking to highlight key aspects of the practical disposition towards organization adopted by classic organization theories and other related approaches throughout the history of organization analysis. In approaching organizational matters in this way, it also attempts to upend the reflex accusation of naivety, rationalism and contemporary irrelevance directed towards the ‘historical artefacts’ of organizational theorizing from the present, and indeed to suggest how classical preoccupations can be applied to pressing matters of contemporary organizational concern without any need to ‘update’ them.